2016
DOI: 10.1089/chi.2015.0214
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Sleep Duration and Indicators of Cardiometabolic Disease in Canadian Children and Adolescents: Analyses of the 2007–2009 Canadian Health Measures Survey

Abstract: Future studies should include longitudinal designs that address whether short sleep duration in boys and in adolescents contributes directly to the development of overweight and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
0
14
0
7
Order By: Relevance
“…In recent time, sleep has been considered to have an impact on weight status among children and adolescents [ 28 30 ]. It has thus been highlighted as a potential target in obesity interventions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent time, sleep has been considered to have an impact on weight status among children and adolescents [ 28 30 ]. It has thus been highlighted as a potential target in obesity interventions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies show linear associations between sleep duration and dyslipidemia; long sleep duration may be a risk factor for dyslipidemia as well, as one study of Korean adolescents found that long sleep duration but not short sleep duration was associated with hypertriglyceridemia,129 and a study of Iranian children and adolescents found that long sleep duration (>8 hours) was associated with higher LDL levels in females and higher total cholesterol levels in males 130. Additionally, several other studies found no significant associations between sleep duration and lipid levels in children and adolescents,131133 and the 2007–2009 Canadian Health Measures Survey found that there were no significant associations between sleep duration and lipid levels after adjusting for body weight 97. Thus, sleep duration (short and/or long) may associate with dyslipidemia in children and adolescents, but the association may be mediated by obesity.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 98%
“…While not every study has found an association between sleep duration and obesity, 91 the majority of cross-sectional and longitudinal studies have shown that insufficient sleep duration in children associates with concurrent or long-term risk of obesity – in infancy, 92 early childhood, 93 95 school-age years, 94 , 96 98 and adolescence. 97 , 99 , 100 A meta-analysis of 13 pediatric studies that included >30,000 children found a pooled OR of 1.89 for obesity in children who were short sleepers. 25 However, short sleep duration may not be the only factor in play: obese children were found to be less likely than their nonobese peers to experience catch-up sleep on the weekends.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 99%
“…However, the relationship between ACS and other individual factors such as aspects of a youth’s health still need to be better clarified. Sleep duration and breakfast consumption could be considered relevant health behaviours in both children and adolescents, due to its link with numerous chronic diseases [2426]. Sufficient sleep duration requirements vary across the lifespan, and from person to person, but it is important to take into account that individuals who habitually sleep outside the normal sleep range may be compromising their health and well-being [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the young population, the recommended range of sleep duration so as not to compromise health is from 9 to 11 and 8 to 10 h in children and adolescents respectively [28]. Recent studies have demonstrated that children and adolescents with short sleep durations had greater odds of being overweight or obese [24, 25], a higher risk of elevated fasting glucose levels [29], and an unhealthier immune profile [30]. Moreover, children who do not usually have breakfast present higher blood markers related to cardiometabolic risk [26].…”
Section: Introductionmentioning
confidence: 99%